2022
DOI: 10.3389/fsufs.2022.911574
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating resistance to mungbean yellow mosaic virus in greengram (Vigna radiata L): Through CRISPR/Cas9 mediated editing of the viral genome

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) associated protein (CRISPR/Cas9) is an adaptive immune system of bacteria to counter the impending viral pathogen attack. With persistent improvements, CRISPR has become a versatile tool for developing molecular immunity against viruses in plants. In the current report, we utilized the Cas9 endonuclease and dual 20 bp-gRNAs targeting two different locations in single-stranded DNA-A of AC1 (rep protein) and AV1 (coat protein) of mungbean yellow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The approach of Kumar et al (2017) and Sahoo et al (2016) of overexpressing a gene originally found in Arabidopsis in mungbean highlights the importance of using knowledge from model species to accelerate mungbean improvement. Gene editing approaches are now available in mungbean and have been applied for biotic stress (Talakayala et al, 2022). One advantage of genome editing is that plants generated with gene knockout strategies (classified as SDN1) are now considered non‐GM in many jurisdictions (Zhang et al, 2021).…”
Section: Breeding For Adaptation To Abiotic Stress In Mungbeanmentioning
confidence: 99%
“…The approach of Kumar et al (2017) and Sahoo et al (2016) of overexpressing a gene originally found in Arabidopsis in mungbean highlights the importance of using knowledge from model species to accelerate mungbean improvement. Gene editing approaches are now available in mungbean and have been applied for biotic stress (Talakayala et al, 2022). One advantage of genome editing is that plants generated with gene knockout strategies (classified as SDN1) are now considered non‐GM in many jurisdictions (Zhang et al, 2021).…”
Section: Breeding For Adaptation To Abiotic Stress In Mungbeanmentioning
confidence: 99%
“…Thus far, CRISPR applications have been shown to be effective against bacterial, viral, and fungi-borne crop diseases, including powdery mildew in wheat and tomatoes, bacterial blight in rice, and bean yellow dwarf virus [80][81][82]. High-quality genome assembly and pan-genome studies to facilitate genetic discovery in mungbean and its improvement Talakayala et al [87] worked on manipulating resistance to mungbean yellow mosaic virus (MYMV) in greengram (Vigna radiata L) through CRISPR/Cas9-mediated editing of the viral genome. In their experiment, these authors confirmed that manipulation of resistance to MYMV through the editing of the pathogen genome using the CRISPR/Cas9 tool can be a powerful approach to combat viruses and develop resistance in greengram.…”
Section: Genomic-assisted Approaches For Promoting Resistance In Mung...mentioning
confidence: 99%
“…Reduced viral infection symptoms and viral RNA accumulation in the genome-edited plants were the results of targeting CMV and TMV with Francisella novicida Cas9 (FnCas9) in combination with particular sgRNAs ( Zhang et al, 2018 ). CRISPR-Cas9 was used to target single-stranded DNA-A of the AV1 and AC1 genes in the Mung bean yellow mosaic virus to enhance resistance in tobacco against this virus ( Talakayala et al, 2024 ). RNA viruses that harm plant cells can be targeted using the CRISPR-Cas13 system in addition to the CRISPR-Cas9 system.…”
Section: Genome Editing For Improving Disease Resistance Against Vira...mentioning
confidence: 99%